Răspunsuri

2014-07-23T12:10:38+03:00
(a,b)=17   =>  a=17m   ∧  b=17n   ;(m;n)=1
a+b=85

17m+17n=85
17(m+n)=85  |:17

m+n= 5

m     n
0      5
1       4
2      3
3      2
2       1
5       0

1)m=0  =>a=0*17=0
n=5  =>b=5*17=85

2)m=1  =>a=1*17=17
n=4  =>b=4*17=68

3)m=2  =>a=2*17=34
n=3  =>b=3*17=51

4)m=3  =>a=3*17=51
n=2  =>b=2*17=34

5)m=4  =>a=4*17=68
n=1  =>b=1*17=17

6)m=5  =>a=5*17=85
n=0  =>b=0*17=0

S={(0;85);(17;68);(34;51);(51;34);(68;17);(85;0)}
bravo
mersi ;)
mersi ca m-ai invatat insfarsit astea :D
ok.. :))